“Il tempo è una lama sottile, che tutto cancella e tutto fa superare”: Retoriche del tempo nei malati terminali di cancro in Hospice - Fantauzzi, Annamaria (Antropologia Pubblica, 2024)
This paper faces on the perception of the time for a terminal cancer patient admitted to the hospice of Aosta (Italy). The project explores the anthropological vision of time, the perception of a patient at the end of his life and the management of care realized by health professionals. Moreover there is an issue about the relationship between the researcher and the context: how to explain the presence of the anthropologist to the patient, to his family and to the team?